IgA‐ and SIgA anti‐PR3 antibodies in serum versus organ involvement and disease activity in PR3‐ANCA‐associated vasculitis. (25th February 2016) - Sandin, C.; Eriksson, P.; Segelmark, M.; Skogh, T.; Kastbom, A.
Summary: Circulating immunoglobulin (Ig)A class anti‐neutrophil cytoplasm antibodies (ANCA) directed against proteinase 3 (PR3) have been reported in ANCA‐associated vasculitis (AAV) with mucosal involvement. However, secretory IgA (SIgA) PR3‐ANCA has not been reported previously. In this study we compared serum levels of SIgA PR3‐ANCA and IgA PR3‐ANCA with IgG PR3‐ANCA in relation to disease characteristics. Among 73 patients with AAV and PR3‐ANCA at diagnosis, 84% tested positive for IgG PR3‐ANCA, 47% for IgA‐ANCA and 36% for SIgA PR3‐ANCA at the time of sampling for the present study. IgA and IgG PR3‐ANCA were represented similarly among patients with different organ manifestations, i.e. upper airway, lung or kidney at time of sampling. However, SIgA PR3‐ANCA was significantly less represented among patients with upper airway involvement. During active disease, the proportions of IgA PR3‐ANCA and SIgA PR3‐ANCA‐positive patients were significantly higher compared to inactive disease. Eight patients were sampled prospectively during 24 months from onset of active disease. In these patients, IgA PR3‐ANCA and SIgA PR3‐ANCA turned negative more often after remission induction compared to IgG PR3‐ANCA. Our findings suggest that serum IgA PR3‐ANCA and SIgA PR3‐ANCA are related more closely to disease activity in AAV compared to IgG PR3‐ANCA. Further studies are required to reveal if this has implications for disease activity monitoring. The mean number of PR3‐ANCA isotypes increased along with disease activity, suggesting a global B cell activation during active disease.